AN EXAMINATION OF THE SOCIO-ENVIRONMENTAL EFFECTS OF DEFORESTATION IN ZAMFARA STATE FOREST RESERVES, NIGERIA - Amir, Abdulazeez; Abdulrashid, Ibrahim; Aliyu, Mohammed Shinkafi (FUDMA JOURNAL OF SCIENCES, 2023)
As one of the oldest and most obviously degraded forest reserve in Zamfara State, Marbe Forest was selected as a case study to determine the magnitude, causes and effects of deforestation in Zamfara State. Interview and questionnaire survey were employed to determine factors causing deforestation. Satellite Imagery analysis was employed to determine the magnitude of deforestation in the forest. Land use and land cover analyses of satellite imageries covering the periods 1980 (Landsat MSS) and 2015 (QUICKBIRD) using ERDAS IMAGINE and Arc GIS 9.3 software showed that forest vegetation had the highest percentage decline rate of 91.25% over a 35 year period. The factors responsible for the menace of deforestation in the forest were found to be the indiscriminate destruction of forest for agricultural expansion by the government, encroachment by illegal timber and fuel wood collectors and insecurity. General findings of the research reveal that the menace brought about by deforestation in the area has been enormous and unprecedented. The research concluded that, Marbe Forest Reserve no longer possess the basic characteristics of a forest, let alone a forest reserve. Unchecked deforestation over the years has deprived the forest of its tree resources; and with the current trend, the forest may no longer exist in the next five to ten years. The research recommends that concerted efforts be made by the government to reclaim the deforested area and measures including reforestation and strict surveillance be initiated to replace the lost natural habitat and prevent it from further degradation.